Exploring Patients’ Experiences of Hospital Administrative Services: A Patient Experience Perspective - Asdi Lastari (Jurnal Ilmu Kesehatan Nusantara, 2026)
Background: Hospital administrative services influence accessibility, continuity, trust, and patients’ overall perceptions of healthcare. Fragmented procedures, uncertain waiting times, inconsistent information, and unequal digital access may create significant barriers, even when clinical care is adequately delivered. Research Objective: This study aimed to explore patients’ experiences of administrative services at RSUD Daya Makassar from a patient experience perspective. Methods: A qualitative descriptive study was conducted from May to July 2025. Eighteen patients were recruited through purposive sampling. Data were collected using face-to-face, semi-structured interviews addressing registration, document verification, waiting times, staff communication, digital systems, service coordination, and complaint handling. The data were analysed thematically. Trustworthiness was maintained through triangulation, member checking, peer debriefing, reflexive notes, and an audit trail. Results: Five themes were identified: administrative services as a complex patient journey; waiting time and procedural uncertainty; the importance of responsive and empathetic communication; unequal experiences with digital services; and expectations for integrated and humane administration. Positive experiences occurred when patients received clear information, respectful assistance, and coordinated services. Negative experiences were associated with repeated procedures, unclear queues, inconsistent information, and limited assistance for older adults and patients with low digital literacy. Conclusion: Hospital administrative quality is determined by efficiency, communication, integration, and accessibility. RSUD Daya Makassar should simplify procedures, provide transparent queue information, strengthen staff communication, integrate digital and on-site services, and ensure assistance for vulnerable patients.